Thermal Analysis of Air-Core Power Reactors. (24th March 2013) - Yuan, Zhao; He, Jun-jia; Pan, Yuan; Yin, Xiao-gen; Ding, Can; Ning, Shao-fei; Li, Hong-lei
Abstract : A fluid-thermal coupled analysis based on FEM is conducted. The inner structure of the coils is built with consideration of both the structural details and the simplicity; thus, the detailed heat conduction process is coupled with the computational fluid dynamics in the thermal computation of air-core reactors. According to the simulation results, 2D temperature distribution results are given and proved by the thermal test results of a prototype. Then the temperature results are used to calculate the heat flux to predict the detailed heat transfer process in the packages of the reactors. The study in this paper may be useful in the design optimization in air-core reactors.